TI_GERICHTE 12.2018.119 vom 4. November 2019 , Lavoro - licenziamento in tronco - restituzione di anticipi salariali - TI Tribunale d'appello (2019)
Lavoro - licenziamento in tronco - restituzione di anticipi salariali